Analysis of Education Programs in New Zealand: Analisis Program Pendidikan di Selandia Baru - Saputra, Andra; Fitri, Nidya; Ananda, Azwar; Rusdinal, Rusdinal; Gistituati, Nurhizrah (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2024)
This research analyzes educational programs in New Zealand through a comprehensive literature study, focusing on educational policies, curriculum structures, teaching methods, as well as challenges and solutions in overcoming educational gaps. The results show that education policy in New Zealand is very progressive and innovative, with initiatives such as